Study of Metallo β- lactamase producing Pseudomonas aeruginosa in diabetic foot infections - Anjali Sunildatta Jog (International Journal of Medical Research and Review, 2015)
Introduction: Pseudomonas aeruginosa , gram negative aerobic rod, is an opportunistic and worrisome nosocomial pathogen. Metallo β- lactamase (MBL) mediated resistance to carbapenems is an emerging threat. Foot ulcers in diabetics are prone to polymicrobial infections. Infection with such multidrug resistant organisms increases morbidity and mortality in these patients.Materials and methods: Present study was undertaken to find out metallo β- lactamase producing Pseudomonas aeruginosa in diabetic foot infections. The study period was October 2009 – August 2011. Samples from the wounds of 121 Type II diabetic patients with foot infection were studied. P. aeruginosa isolates were identified by conventional methods. Antibiotic susceptibility testing of these isolates was done by Kirby- Bauer Disk Diffusion method. The isolates showing resistance to imipenem were subjected to EDTA- Disk Synergy test (EDS) and Imipenem – EDTA Combined Disk method for metallo β- lactamase detection. Minimum Inhibitory Concentration (MIC) of imipenem and imipenem- EDTA was determined in these isolates by agar dilution method.Results: Total 139 isolates were obtained from the samples. Out of which 22 isolates were of Pseudomonas aeruginosa (15.82%). Metallo β- lactamase production was seen in 12 isolates (54.54%) by both the tests.Conclusion: It is concluded that prevalence of metallo β- lactamase producing Pseudomonas aeruginosa in diabetic foot infection was 54.54%. Continuous surveillance of such resistant strains will help the clinician to facilitate the development of effective strategies to combat growing problem of resistance.